Learning From Communities' Involvement in the Management of Parks: The Case of Zoo Lake and Thokoza Park, Johannesburg - Hadebe, Sizakele (University of the Witwatersrand, Johannesburg, 2015)
communityToday officials within Johannesburg City Parks and Zoo face the daunting challenge of delivering high quality public spaces that have meanings that are stable enough to accommodate the cultural diversity and social polarisation that are inherent in contemporary Johannesburg. This report examines a recent trend towards joint management of public spaces, where responsibilities are shared between the state and communities interested in these spaces along the lines of what Jones (2010) has called the “Friends of the Park” (FOP). It is argued in this report, with reference to Don Mitchell’s (1995) work with People’s Park in San Diego, that instances where a particular public space is perceived to be in decline are a reflection of contradictions within that public space’s socio-cultural dimension where the introduction of new activities or a new kind of user into the space conflicts with the commonly held meaning of the space. Such a space would thus be characterised by a crisis of meaning. Although the meaning of public space is contested, there is a tendency over time to move towards a stability of meaning, referred to in this report as consensus. While it usually resolves the crisis of meaning, this consensus does not necessarily mean a shift towards justice or towards an equitable end (Castells, 2003). Without making any value judgements on the end result, by studying FOPs’ efforts to engage with the management of parks, this research essentially seeks to understand how actors (members of the community, employees of the state, political activists and others) work towards this kind of consensus. It is noted in this research that an FOP approach risks romanticising participation by thinking of the transition from invented spaces to invited spaces as being organic, natural and perhaps even inevitable; and thereby overlooking the fact that invented spaces today exist in the context of deliberate efforts by planners to mobilise communities for the purpose of absorbing them into the formal planning structure. In the context of neoliberalism it could be said then that such an approach to park management might allow governments to dump their responsibilities on the communities they are meant to serve.
Planning Honours Research Report 2015, Wits University
Keywords: community mobilisation, public spaces, Thokoza Park, Zoo Lake, park management